Effects of nitrogen nutrition on soluble osmotica in rice plants in response to drought stress - ZHU Wei-qin; WU Liang-huan; TAO Qin-nan (浙江大学学报. 农业与生命科学版, 2003)
The effect of nitrogen nutrition on soluble osmotica in rice plants grown under polyethylene glycol (PEG)-induced drought stress was studied. The results showed that moderate nitrogen nutrition could promote the accumulation of free proline and total free amino acid in leaves of Brazilian upland rice which belongs to drought resistant varieties, although it had no significant effect on conventional rice variety Zhongxiang 1. Adequate nitrogen supply led to decrease in soluble sugar content of leaves in both varieties. As changes of inorganic osmotica content in rice plants stressed by drought was concerned, potassium ion was the main osmoticum, moreover, moderate nitrogen nutrition could promote the accumulation of potassium ion in both rice shoots.